Cervical rupture in the pregnant woman who has cervical cerclage: Case report and literature review - Güngör, Sami; Kavak, Burçin; Çelik, Hüsnü (My University, 2012)
Cervical insufficiency is the failure of the cervix to carry pregnancy till term due to its' structural and functional weakness. Patients who underwent cervical cerclage should be monitored closely fort he possibility of infection and rupture of membranes.Patients with the symptom of continous and non specific pain should be evaluated for cervical rupture. A 22 week pregnant patient with cervical cerclage applied to our clinic with vaginal bleeding and abdominal pain. In physical examination active flow of amniotic fluid was determined and in the to comete r no uterine contraction was determined. 4 hours after follow up cervical rupture was determined. The pregnancy was terminated by laparotomy and after termination of pregnancy cervical rupture was repaired vaginally.According to our experience in patients with cervical rupture, the pregnancy must be terminated by laparotomy and the cervical rupture must be repaired vaginally thereafter. Copyright © 2012 by Türkiye Klinikleri.
Servikal serklaji olan bir gebede servikal rüptür: Olgu sunumu ve literatürün gözden geçirilmesi
Keywords: Cerclage, cervical; Pregnancy; Uterine rupture